2012
DOI: 10.1074/jbc.m111.264473
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Increased Toxicity of Pathological Aβ42:Aβ40 Ratios in Alzheimer Disease

Abstract: Background: Amyloid ␤ peptide plays a role in Alzheimer disease. Results: Interaction of amyloid ␤ peptides with 40 and 42 amino acids has consequences for oligomer formation. Conclusion: Increased production of amyloid ␤ peptide with 42 amino acids affects the behavior of the entire amyloid ␤ peptide pool. Significance: This might explain the synaptotoxic effect observed with a shift in amyloid ␤ peptide production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
226
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(244 citation statements)
references
References 43 publications
16
226
1
1
Order By: Relevance
“…In apparent contrast, previous in vitro studies have reported that assemblies of Ab protofibrils with different Ab40/42 ratios have similar molecular structures [27,28]. However, in vivo and within a cellular environment Ab aggregation is likely different [10].…”
Section: Transmission Of Ab Morphotypesmentioning
confidence: 73%
“…In apparent contrast, previous in vitro studies have reported that assemblies of Ab protofibrils with different Ab40/42 ratios have similar molecular structures [27,28]. However, in vivo and within a cellular environment Ab aggregation is likely different [10].…”
Section: Transmission Of Ab Morphotypesmentioning
confidence: 73%
“…By using this method, we successfully decoupled the aggregation from the HDX process. Importantly, we extracted kinetic information on the Aβ 42 aggregation at 25°C, indicating that the middle region of the Aβ 42 peptide (i.e., [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] was the "seeding" region in aggregation, followed by the C-terminus hydrophobic region (i.e., [36][37][38][39][40][41][42] and then the N-terminus hydrophilic region (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Finally, we showed that this approach allowed us to examine directly the factors that affect the oligomerization of Aβ 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Upon pulsed HDX of the preformed fibrils we observed both the peptides formed by pepsin digestion (i.e., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and the undigested Aβ 42 . The peptides and the full Aβ 42 are similarly protected (89 ± 1% for the undigested Aβ 42 and 85 ± 1%, 84 ± 1%, and 91 ± 2% for 1-19, 20-35 and 36-42, respectively), consistent with the peptides' being proteolytic fragments from the amyloid fibrils.…”
Section: Application Of Finke-watzky Modeling and Statistical Evaluatmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various Aβ fragments, such as 1-28, 25-35, and 34-42, have shown similar biochemical and biophysical properties to fulllength Aβ, 12-14 the establishment of structural models of fulllength Aβ has been desired because full-length Aβ is responsible for the pathogenesis of AD. [15][16][17][18] Here, we investigated the secondary structure of aggregated Aβ(1-40) and Aβ in an aqueous environment with VCD spectroscopy. VCD spectroscopy, where one measures the circular dichroism activity in the molecular vibration region, is a powerful tool for the discrimination of slight differences between secondary structures of peptides and proteins in aqueous environments.…”
Section: Introductionmentioning
confidence: 99%